Cigarette Butts; A Little Leaven That Leaveneth the Whole Lump (Applied Research and Innovation, 2023)
Tobacco The tobacco industry has introduced the most abundant forms of plastic (microplastic) into human waste streams with no intended managerial strategies over the centuries. They have maintained monetary gain but shifted blames to the end users, making butts “it’s small, “it does not matter” the most abundant untamed litters globally. The butts are said to release over 400 carcinogenic chemicals when discarded inhumanly into the environment (air, water and land); with attended effects on the environmental resources and human beings. The basis of this study is to draw public attention and cultural waste management practices towards Cigarette butts in Bayelsa State considering the vast and high ecological sensitivity of the state and the region at large. About 240 pieces of carefully designed schedules covering demographic features, smoking frequencies, awareness, smoking environment and butts management culture were utilized to elucidate the objectives of the study. The chains of smokers were more between the ages of 36-45years and lesser between the ages of 20-25years; 92% of smokers were male making them the most likely gender to litter the environment with cigarette butts; of the totals smokers 67% respondent don’t know that cigarette butts is non-biodegradable and very toxic to the environment. 34% respondent smokes in conspicuous environment; 19% inconspicuous milieu (hideout and ghettos), 23% in controlled designated areas and 24% agreed to smoke in an undesignated environment (Streets). Dumping in trash accounted for 24%, 30% selectively discarded in shops, clubs, malls etc. while 46% admitted to have discarded butts randomly, exposing the environment to arrays of toxins. Therefore, creating awareness is necessary but holding the tobacco companies accountable for butts’ management is very optimal.